THE HUMAN DIMENSIONS OF SOLDERING:A PERSPECTIVE ON FUTURE REQUIREMENTS IN THE COMPLEX OPERATIONAL ENVIRONMENT - Hj Zulkifli bin Hj Zainal Abidin (European Scientific Journal, ESJ, 2014)
For centuries past and likely for centuries to come, military leaders have debated the qualities desired in a soldier. It is easy to find that nearly every prominent military leader and researcher has advocated the importance of attributes such as courage, integrity, perseverance, intelligence, loyalty and self-confidence. All militaries considers the soldier central to mission success and emphasized the importance of better understanding moral, cognitive, and physical aspects of soldier performance across a full spectrum of operations. The human dimension of soldering meets the complex operational environment which exists today and in the near future, with the range of threats during this period extending from smaller, lower-technology opponents using more adaptive, asymmetric methods to larger, modernized forces able to engage forces in more conventional, symmetrical ways. Due to these increasing complexities coupled with rapid state of the art technological advancements, in future soldier technology envisage a different operational environment in the future but without the consideration and understanding of the capabilities of our soldiers both physically, mentally in both moral and cognitive dimensions which will ultimately limit the effectiveness of both the technologies and our soldiers.This paper describes the human dimension as the moral, cognitive, and physical components of soldier and organizational development and states that the Army concepts acknowledge the soldier as the centerpiece of the Army, but none, individually or collectively, adequately addresses the human dimension of future operations.